Aerodynamic study of a modern sepak takraw ball using smoke flow visualization technique - Abdul Syakir, Abdul Mubin (Kementerian Pendidikan Tinggi (KPT), Malaysia, 2018)
Link to publisher's homepage at http://www.mohejournal.com/index.php/mohe